Pollen Germination and Pollen Tube Growth in Gymnosperms - Maria Breygina; Ekaterina Klimenko; Olga Schekaleva (Plants, 2021)
Pollen germination and pollen tube growth are common to all seed plants, but these processes first developed in gymnosperms and still serve for their successful sexual reproduction. The main body of data on the reproductive physiology, however, was obtained on flowering plants, and one should be careful to extrapolate the discovered patterns to gymnosperms. In recent years, physiological studies of coniferous pollen have been increasing, and both the features of this group and the similarities with flowering plants have already been identified. The main part of the review is devoted to physiological studies carried out on conifer pollen. The main properties and diversity of pollen grains and pollination strategies in gymnosperms are described.